2013
DOI: 10.1097/opx.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Orbscan Topography in Primary Open-Angle Glaucoma

Abstract: Primary open-angle glaucoma eyes have a higher elevation of the posterior corneal surface than that in central corneal thickness-matched nonglaucomatous eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Even though it was not initially the main purpose of the study, we found a significant correlation between the nonmedicated mean IOP and the PCE at the preoperative baseline visit, suggesting that mechanical compression of the stroma occurs in POAG eyes with a subsequent increase in the PCE. This finding, which could be a new marker for the biomechanical corneal modifications that occur in glaucoma patients, has been previously described by Arranz-Marquez et al 26 Most likely, corneal hysteresis (CH) and the way it responds to changes in the IOP are involved in the changes encountered in the PCE. CH remains stable with diurnal variations in the IOP 27 or transient corneal swelling induced by contact lenses, 28 thus maintaining biomechanical integrity under these conditions.…”
Section: Discussionsupporting
confidence: 73%
“…Even though it was not initially the main purpose of the study, we found a significant correlation between the nonmedicated mean IOP and the PCE at the preoperative baseline visit, suggesting that mechanical compression of the stroma occurs in POAG eyes with a subsequent increase in the PCE. This finding, which could be a new marker for the biomechanical corneal modifications that occur in glaucoma patients, has been previously described by Arranz-Marquez et al 26 Most likely, corneal hysteresis (CH) and the way it responds to changes in the IOP are involved in the changes encountered in the PCE. CH remains stable with diurnal variations in the IOP 27 or transient corneal swelling induced by contact lenses, 28 thus maintaining biomechanical integrity under these conditions.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, we can conclude that CCT values differ between populations and genders. These facts should be considered when performing applanation tonometry and refractive surgery [ 4 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glaucoma can modify the cornea. The posterior corneal surface is more elevated in patients with glaucoma than in healthy subjects [6], lowering the IOP in steroid-induced glaucoma decreases the posterior corneal elevation and the CCT [7] and IOP elevation produces refractive changes in patients who underwent a previous corneal laser refractive surgery [8].…”
Section: Introductionmentioning
confidence: 99%